2018
DOI: 10.1002/jaba.500
|View full text |Cite
|
Sign up to set email alerts
|

The Good Behavior Game in preschool classrooms: An evaluation of feedback

Abstract: The Good Behavior Game (GBG) is a popular group contingency implemented to decrease disruptive behavior in classrooms. However, despite numerous replications of the GBG, there are few direct comparisons evaluating the effectiveness of specific components of the GBG. In the present study, we directly compared the type of feedback delivered during the GBG on the effectiveness of the GBG to reduce disruptive behavior in two preschool classrooms. Results showed that delivering vocal feedback (e.g., "raise your han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 17 publications
1
20
0
1
Order By: Relevance
“…Occasionally, when the teacher removed a token without providing vocal feedback, the students looked at each other and expressed signs of confusion (e.g., raising both shoulders up, looking around to identify the student who broke a rule) indicating that vocal feedback is likely an important component in the treatment package. In fact, Wiskow et al (2019) found that vocal feedback was a critical component to reduce disruptions during the GBG in preschool classrooms. Removing a token only indicates that a student engaged in disruption, whereas vocal feedback specifies the topography of the disruption and who violated the rule (e.g., "Team 1, raise your hand"), and may be more salient.…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, when the teacher removed a token without providing vocal feedback, the students looked at each other and expressed signs of confusion (e.g., raising both shoulders up, looking around to identify the student who broke a rule) indicating that vocal feedback is likely an important component in the treatment package. In fact, Wiskow et al (2019) found that vocal feedback was a critical component to reduce disruptions during the GBG in preschool classrooms. Removing a token only indicates that a student engaged in disruption, whereas vocal feedback specifies the topography of the disruption and who violated the rule (e.g., "Team 1, raise your hand"), and may be more salient.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, studies of interdependent group contingencies consistently show that problem behavior does not decrease without programmed consequences for rule adherence and within-session feedback for rule violations in children (e.g., Greenwood, Hops, Delquadri, & Guild, 1974; Wiskow, Matter, & Donaldson, 2019) and adolescents (Brogan, Falligant, et al, 2017; Hernan et al, 2018; McDougale et al, 2018). To our knowledge, no study of either group or classroom procedures has shown that rules without programmed consequences for rule adherence either decrease problem behavior or increase appropriate behavior.…”
mentioning
confidence: 81%
“…It is possible that after exposure to the whole GBG-package, the omission of feedback may produce similar effects on behavior as when feedback is provided. Wiskow et al (2019) conducted a more comprehensive study on GBG feedback in a preschool setting. Rather than completing a full component analysis of the GBG, the authors compared four types of feedback: no feedback, visual feedback, vocal feedback or visual + vocal feedback.…”
Section: Research-article2020mentioning
confidence: 99%